2014
DOI: 10.1039/c4ja00176a
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution continuum source graphite furnace atomic absorption spectrometry for direct analysis of solid samples and complex materials: a tutorial review

Abstract: This work tries to provide guidance for the development of new methods aiming at the direct analysis of solid samples or complex liquid materials using HR CS GFAAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 107 publications
(191 reference statements)
0
44
0
3
Order By: Relevance
“…Still, the experiments carried out with the solid samples demonstrated that it is difficult to properly atomize the target elements from this refractory matrix [28,40,41]. The signal obtained showed a very long tail that did not return to the baseline, even when a long atomization time (20 s) and a high atomization temperature are selected (2600°C).…”
Section: Optimization Of the Working Conditions For The Analysis Of Tmentioning
confidence: 89%
See 3 more Smart Citations
“…Still, the experiments carried out with the solid samples demonstrated that it is difficult to properly atomize the target elements from this refractory matrix [28,40,41]. The signal obtained showed a very long tail that did not return to the baseline, even when a long atomization time (20 s) and a high atomization temperature are selected (2600°C).…”
Section: Optimization Of the Working Conditions For The Analysis Of Tmentioning
confidence: 89%
“…Optimization of the working conditions for the analysis of active pharmaceutical ingredients This sample represents the opposite situation for SS GFAAS analysis in comparison with the car catalysts. Most of the matrix consists of organic compounds that can be eliminated with ease during the pyrolysis step, leaving the analytes ready for a selective atomization [28,40]. This was the case in the few previous applications focused on the analysis of other pharmaceutical products by means of traditional line source SS GFAAS [44,49].…”
Section: Analysis Of Active Pharmaceutical Ingredientsmentioning
confidence: 97%
See 2 more Smart Citations
“…Para a análise de sólidos, espera-se que as condições aplicadas a líquidos não sejam compatíveis aos sólidos. Geralmente, são necessários pré-tratamentos, seleção de massa de amostra, avaliação dos parâmetros instrumentais para análise de sólidos, otimização da vaporização (o analito não está disponível como em amostras líquidas), e finalmente o padrão a ser aplicado [48]. Em conjunto a estes problemas, soma-se a possibilidade de aplicação de ID neste sistema, a qual não possui registros de ter sido aplicada para GFMAS.…”
Section: Avaliação Do Sinal Do Deslocamento Isotópicounclassified